Application of aldehyde group organic composite material and optimized ester-ether hybrid electrolyte to potassium ion battery
Through the combination of aldehyde-based organic composite materials and optimized ester ether hybrid electrolyte, the poor conductivity and interface compatibility of organic negative electrode materials in potassium ion batteries are solved, and higher battery performance and safety are achieved.
Patent Information
- Application Number
- CN202410682997.7
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-05-29
- Publication Date
- 2024-12-20
AI Technical Summary
The organic negative electrode materials of existing potassium ion batteries have poor conductivity, are easily soluble in electrolytes, and have low volume energy density, resulting in limited battery performance. In addition, traditional electrolytes have interface compatibility problems during charging and discharging, which affects cycle stability and safety. .
The organic negative electrode was prepared by heat treatment of 2-bromobenzene-1,3-diformaldehyde and multi-wall carbon nanotubes using aldehyde-based organic composite materials and optimized ester ether hybrid electrolytes, and the ester ether hybrid solvents such as EC+DME were used. , PC+DME, VC+DME are combined with bisfluorosulfonimide potassium salt (KFSI), which regulates the potassium salt concentration and solvation structure to improve the conductivity of the electrode material and the compatibility of the electrolyte.
The specific capacity, cycle stability and reaction kinetics of the organic negative electrode are improved, the cycle stability and thermal stability of the battery are enhanced, the dissolution behavior is reduced, and the safety performance and Coulomb efficiency of the battery are improved.
Smart Images

Figure CN119170856A_ABST
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field of organic negative electrode materials and electrolytes, and in particular relates to an aldehyde-based organic composite material and an optimized ester-ether hybrid electrolyte for a potassium ion battery. Background Art
[0002] Potassium-ion batteries have become a promising large-scale energy storage technology worldwide. Potassium-ion batteries (PIBs) are ideal candidates for large-scale energy storage due to their uniform global distribution of potassium sources, high diffusion kinetics of ions in organic electrolytes, similar energy density and power density to lithium-ion batteries, and similar working principles. Therefore, it is urgent to develop the next generation of renewable energy storage technology based on PIBs.
[0003] As the "blood" of PIBs, electrolyte plays a decisive role in the electrochemical performance of the device (including capacity, cycle performance, rate performance, and working potential). According to the type of solvent used, ester-based electrolytes and ether-based electrolytes are representative in alkali metal ion batteries. Generally speaking, ester-based electrolytes have excellent electrochemical properties and high ionic conductivity; while ether-based electrolytes generally have high solubility for metal salts, which can ensure that ether molecules are tightly bound to cations and increase the stability of the system. However, electrolytes with a single type of solvent often have serious interfacial compatibility problems. Traditional carbonate electrolytes will continue to decompose at the electrode / electrolyte interface during charging and discharging, forming an uneven solid electrolyte membrane (SEI), resulting in severe capacity decay and low coulombic efficiency (CE). Due to the disordered electrolyte structure, most common ether-based electrolytes still cannot achieve high CE and long-term cycling. In addition, poor oxidation stability and safety are also issues that cannot be ignored for ether-based electrolytes. The single type of solvents in these electrolytes and the unstable interfacial electrochemical properties greatly limit the performance of related batteries.
[0004] In 1984, Tobishima et al. first studied ester-ether mixed electrolytes (EEHE) in lithium-ion batteries. They demonstrated the enhanced conductivity of the EC+DME (1:1) mixed system and successfully revealed a new film-forming mechanism based on the decomposition of Li(EC)y1(DME)y2Cn graphite-doped compounds (GICs) and the subsequent construction of a protective layer on graphite, which effectively prevented further co-intercalation of the solvent, thereby achieving stable interfacial electrochemistry. The EC+DME mixed system containing lithium and sodium salts also exhibited a unique solubility structure in which cations preferentially bind to DME, which is opposite to the EC-dominated solvation structure in typical EC-containing ester-based electrolytes. These findings provide a good guide for the design of advanced PIBs electrolytes.
[0005] Compared with other developed potassium ion battery electrode materials, organic electrode materials are mainly composed of lightweight and cheap elements such as C, H, O, N and S, and have the advantages of high cost-effectiveness and structural design at the molecular level. Since 2017, Fan and his collaborators first reported the application of potassium terephthalate (K2TP) as a small molecule organic electrode in PIBs. A large number of organic anode materials containing various redox-active functional groups have been developed for PIBs, such as 1,1-biphenyl-4,4-dicarboxylate (K2BPDC), 2,2-bipyridine-5,5-potassium dicarboxylate (K2C 12 H6N2O4), 2,5-dihydroxy-1,4-benzoquinone potassium salt (K2C6H2O4), vitamin K, tetrapotassium pyrrolidone (K4PM). However, organic negative electrode materials usually have intrinsic problems such as poor electronic conductivity, solubility in organic electrolytes and low volume energy density, which seriously restrict the widespread development and application of such electrode materials. Therefore, there are still great challenges in designing highly compatible organic anode / electrolyte systems to solve their intrinsic problems and interfacial electrochemical problems. Summary of the invention
[0006] In view of the above problems existing in the prior art, the technical problem to be solved by the present invention is to provide an aldehyde-based organic composite material and an optimized ester-ether hybrid electrolyte for potassium ion batteries, which improves the compatibility of the electrolyte and the electrode interface while improving the conductivity of the electrode material, inhibiting the dissolution of the electrode material, and improving the safety performance of the battery, and accelerates the reaction kinetics and improves the potassium storage performance of the organic composite material.
[0007] The technical solution to achieve the purpose of the present invention is:
[0008] An aldehyde-based organic composite material and an optimized ester-ether hybrid electrolyte are used for a potassium ion battery, characterized in that the potassium ion half-cell comprises potassium metal, an electrolyte, and an organic negative electrode composite material; the organic negative electrode is prepared by heat treatment with 2-bromobenzene-1,3-dicarboxaldehyde (BBD) and multi-walled carbon nanotubes (CNT); and the electrolyte is an ester-ether hybrid electrolyte of potassium bis(fluorosulfonyl)imide (KFSI).
[0009] The aldehyde-based organic composite material and the optimized ester-ether hybrid electrolyte are used for potassium ion batteries. The aldehyde-based organic composite material is prepared by mixing and grinding 2-bromobenzene-1,3-dicarboxaldehyde and multi-walled carbon nanotubes (CNT) in a mass ratio of 1:1, transferring the mixture to a Schlenk tube, replacing the argon atmosphere, and setting the temperature to the melting point range of the organic matter, 139-144°C during heat treatment.
[0010] The aldehyde-based organic composite material and the optimized ester-ether hybrid electrolyte are used in potassium ion batteries, and an ester-ether hybrid solvent is used: commonly used ethylene carbonate (EC), propylene carbonate (PC) or vinylene carbonate (VC) is selected as a base solvent; ethylene glycol dimethyl ether (DME) is used as an ether-based solvent. Unused esters and ethers are mixed in equal volumes to form an ester-ether mixed solvent, which are recorded as EC+DME, PC+DME and VC+DME respectively.
[0011] The aldehyde-based organic composite material and the optimized ester-ether hybrid electrolyte are used for potassium ion batteries. The electrolyte is prepared by adding KFSI to EC+DME, PC+DME and VC+DME in a glove box filled with argon, respectively, and stirring to obtain a potassium ion battery electrolyte with a concentration of 1 mol / L.
[0012] The aldehyde-based organic composite material and the optimized ester-ether hybrid electrolyte are used in potassium ion batteries, and the solvation structure is regulated by weighing salts of different masses to control the molar concentration. The prepared electrolyte concentrations are 1.0 mol / L, 3.0 mol / L, 5.0 mol / L, and 7.0 mol / L, respectively, and the optimal electrolyte concentration is 5.0 mol / L.
[0013] Compared with the prior art, the present invention has the following beneficial effects:
[0014] The present invention explores a novel potassium storage organic negative electrode, in which 2-bromobenzene-1,3-dicarboxaldehyde and potassium ions act on the C=O double bond to achieve reversible potassium storage.
[0015] The present invention uses a one-step pyrolysis treatment when preparing the organic negative electrode material to disperse the organic small molecule substances on the surface and inside of the multi-walled carbon nanotubes. The introduction of carbon nanotubes can improve the conductivity of the system and alleviate the dissolution behavior of organic small molecule substances in the electrolyte through the interaction between carbon tubes and organic molecules.
[0016] The electrolyte composition of the present invention contains an ester-ether hybrid electrolyte, and the electrolyte is configured by adjusting different ester-based solvents to achieve good compatibility between the electrolyte and potassium metal. The ester-ether hybrid solvents are EC+DME, PC+DME and VC+DME, and the potassium salt is potassium bis(fluorosulfonyl)imide (KFSI), wherein the potassium salt concentration is 1.0 mol / L.
[0017] Due to the similar compatibility between the organic anode and the electrolyte and the fact that many side reactions will cause the organic anode to dissolve and shuttle in the electrolyte, the optimization of the electrolyte needs to be taken into account while designing the material structure; on the basis of achieving good compatibility with potassium metal and reversible potassium storage in BBD, the potassium salt concentration and solvation structure are regulated to configure 1.0 mol / L, 3.0 mol / L, 5.0 mol / L and 7.0 mol / L KFSI / EC+DME.
[0018] The present invention effectively improves the specific capacity, cycle stability and reaction kinetics of 2-bromobenzene-1,3-dicarboxaldehyde through organic negative electrode structure design and electrolyte optimization strategy. Optimizing the solvation structure dominated by AGG in the ester-ether hybrid electrolyte is conducive to achieving good potassium metal compatibility and interfacial stability of the organic negative electrode, which is conducive to improving the cycle stability of the battery. In addition, an appropriate increase in potassium ion concentration can improve the thermal stability of the system and reduce the dissolution behavior of 2-bromobenzene-1,3-dicarboxaldehyde in the electrolyte. BRIEF DESCRIPTION OF THE DRAWINGS
[0019] Figure 1 XRD and IR spectra of PTA / CMK3 composites Figure 1 Schematic diagram of the structure of the synthesized organic composite material;
[0020] Figure 2 XRD and IR spectra, thermogravimetric curves and scanning electron microscopy images of the synthesized BBD / PTA composites;
[0021] Figure 3 The possible potassium storage behavior of BBD organic electrode materials;
[0022] Figure 4 The charge and discharge curves of K||Cu and K||K batteries in different ester-ether hybrid electrolytes;
[0023] Figure 5 Raman spectra of EC and FSI- in KFSI / EC+DME electrolytes with different concentrations (a), Raman spectra of DME (b), radial distribution function and coordination number of 5M electrolyte (c) and possible solvation structure diagram (d);
[0024] Figure 6 Comparison of the Coulombic efficiency of K||Cu cells in 1M and 5M KFSI / EC+DME electrolytes (a), the stripping curves of potassium metal plating at different current densities (b), and the time-voltage curves of K||K symmetric cells (c);
[0025] Figure 7 The charge and discharge curves of BBD / CNT in different ester-ether hybrid electrolytes;
[0026] Figure 8 The charge and discharge curves of BBD / CNT in KFSI / EC+DEM ester-ether hybrid electrolytes with different concentrations;
[0027] Fig. 9 The long cycle performance and rate performance diagram of BBD / CNT in KFSI / EC+DEM ester-ether hybrid electrolyte with different concentrations;
[0028] Fig.10 The dissolution UV and visible light images of BBD / CNT in KFSI / EC+DEM ester-ether hybrid electrolyte systems with different concentrations (a) and the combustion experiment image of the response electrolyte;
[0029] Fig.11 Pseudocapacitive contribution (a), overpotential (b), diffusion coefficient (c), EIS before cycling (d), EIS after 50 cycles (e) and Rct fitting value of BBD / CNT in different electrolytes. DETAILED DESCRIPTION
[0030] Example 1
[0031] An aldehyde-based organic composite material and an optimized ester-ether hybrid electrolyte are used for a potassium ion battery. The potassium ion half-cell comprises potassium metal, an organic negative electrode, and an electrolyte. The organic negative electrode is prepared by heat treatment using 2-bromobenzene-1,3-dicarboxaldehyde and multi-walled carbon nanotubes (CNT) as raw materials. The electrolyte is a bis(fluorosulfonyl)imide potassium salt ester-ether hybrid electrolyte. The specific steps are as follows:
[0032] The method for preparing an organic composite negative electrode comprises the following steps:
[0033] (1) Add equal weights of multi-walled carbon nanotubes (CNT) and 2-bromobenzene-1,3-dicarboxaldehyde (BBD) into a quartz mortar and grind for 20 min. (2) The ground mixture was transferred to a Schlenk tube, and the air in the tube was replaced with Ar atmosphere. (3) Subsequently, it was placed in a forced air oven and heated at 140°C for 12 h to obtain a BBD / CNT composite material. The organic negative electrode was able to achieve reversible cycling performance.
[0034] Figure 1 Schematic diagram of the synthesis of BBD / CNT composites. Figure 2 XRD, infrared spectrum, thermogravimetric analysis curve and SEM picture; Figure 2 As shown, a simple thermal treatment achieved the encapsulation of BBD by CNTs, where BBD accounted for 42.3% of the total composite.
[0035] Figure 3 The reaction energy of BBD in the K storage process was calculated and simulated by density functional theory. Figure 3 As shown, K + The binding with BBD mainly involves two processes. First, BBD gains an electron to open a C=O bond and binds to a K + It then gains another electron, opens another C=O bond, and combines with another K + Combine to form K2-BBD.
[0036] Preparation of potassium bis(fluorosulfonyl)imide (KFSI) ester-ether hybrid electrolyte, specifically:
[0037] In a glove box filled with argon atmosphere (water content less than 0.01 ppm, oxygen content less than 0.01 ppm), 0.5 g of ethylene carbonate (EC) and 0.5 ml of ethylene glycol dimethyl ether (DME) were stirred and mixed, 1 mmol of potassium bis(fluorosulfonyl)imide was added to the ester-ether mixed system, and after stirring evenly, 1.0 mol / L KFSI / EC+DME (1 M KFED) ester-ether hybrid electrolyte was obtained.
[0038] K‖K and K||Cu batteries were assembled using 1M KFED ester-ether hybrid electrolyte, and the compatibility of this electrolyte with metallic potassium was studied.
[0039] The BBD / CNT composite material synthesized above was used to assemble a potassium ion half-cell using 1M KFED ester-ether hybrid electrolyte, and the potassium storage performance of the synthesized BBD / CNT composite material in 1M KFED ester-ether hybrid electrolyte was studied.
[0040] Example 2
[0041] In a glove box filled with argon atmosphere (water content less than 0.01 ppm, oxygen content less than 0.01 ppm), 0.5 g of propylene carbonate (PC) and 0.5 ml of DME were stirred and mixed, 1 mmol of potassium bis(fluorosulfonyl)imide was added to the ester-ether mixed system, and after stirring evenly, 1.0 mol / L KFSI / PC+DME (1M KFPD) ester-ether hybrid electrolyte was obtained.
[0042] K||K and K||Cu batteries were assembled using 1M KFPD ester-ether hybrid electrolyte to study the compatibility of this electrolyte with metallic potassium.
[0043] The BBD / CNT composite material synthesized above was used to assemble a potassium ion half-cell using 1M KFPD ester-ether hybrid electrolyte, and the potassium storage performance of the synthesized BBD / CNT composite material in 1M KFPD ester-ether hybrid electrolyte was studied.
[0044] Example 3
[0045] In a glove box filled with argon atmosphere (water content less than 0.01 ppm, oxygen content less than 0.01 ppm), 0.5 g of vinyl carbonate (VC) and 0.5 ml of DME were stirred and mixed, 1 mmol of potassium bis(fluorosulfonyl)imide was added to the ester-ether mixed system, and after stirring evenly, 1.0 mol / L KFSI / VC+DME (1M KFVD) ester-ether hybrid electrolyte was obtained.
[0046] K‖K and K||Cu batteries were assembled using 1M KFVD ester-ether hybrid electrolyte, and the compatibility of this electrolyte with metallic potassium was studied.
[0047] A potassium ion half-cell was assembled using the BBD / CNT composite material synthesized above using 1M KFVD ester-ether hybrid electrolyte, and the potassium storage performance of the synthesized BBD / CNT composite material in 1M KFVD ester-ether hybrid electrolyte was studied.
[0048] Example 4
[0049] In a glove box filled with argon atmosphere (water content less than 0.01 ppm, oxygen content less than 0.01 ppm), 0.5 g of EC and 0.5 ml of DME were stirred and mixed, 3 mmol of potassium bis(fluorosulfonyl)imide was added to the ester-ether mixed system, and after stirring evenly, 3.0 mol / L of KFSI / EC+DME (3M KFED) ester-ether hybrid electrolyte was obtained.
[0050] K||K and K||Cu batteries were assembled using 3M KFED ester-ether hybrid electrolyte, and the compatibility of the electrolyte with metallic potassium was studied.
[0051] The BBD / CNT composite material synthesized above was used to assemble a potassium ion half-cell using 3M KFED ester-ether hybrid electrolyte, and the potassium storage performance of the synthesized BBD / CNT composite material in 3M KFED ester-ether hybrid electrolyte was studied.
[0052] Example 5
[0053] In a glove box filled with argon atmosphere (water content less than 0.01 ppm, oxygen content less than 0.01 ppm), 0.5 g of EC and 0.5 ml of DME were stirred and mixed, 5 mmol of potassium bis(fluorosulfonyl)imide was added to the ester-ether mixed system, and after stirring evenly, 5.0 mol / L of KFSI / EC+DME (5M KFED) ester-ether hybrid electrolyte was obtained.
[0054] K||K and K||Cu batteries were assembled using 5M KFED ester-ether hybrid electrolyte, and the compatibility of this electrolyte with metallic potassium was studied.
[0055] A potassium ion half-cell was assembled using the BBD / CNT composite material synthesized above using 5M KFED ester-ether hybrid electrolyte, and the potassium storage performance of the synthesized BBD / CNT composite material in 5M KFED ester-ether hybrid electrolyte was studied.
[0056] Example 6
[0057] In a glove box filled with argon atmosphere (water content less than 0.01 ppm, oxygen content less than 0.01 ppm), 0.5 g of EC and 0.5 ml of DME were stirred and mixed, 7 mmol of potassium bis(fluorosulfonyl)imide was added to the ester-ether mixed system, and after stirring evenly, 7.0 mol / L of KFSI / EC+DME (7M KFED) ester-ether hybrid electrolyte was obtained.
[0058] K||K and K||Cu batteries were assembled using 7M KFED ester-ether hybrid electrolyte, and the compatibility of this electrolyte with metallic potassium was studied.
[0059] The BBD / CNT composite material synthesized above was used to assemble a potassium ion half-cell using 7M KFED ester-ether hybrid electrolyte, and the potassium storage performance of the synthesized BBD / CNT composite material in 7M KFED ester-ether hybrid electrolyte was studied.
[0060] The performance test results of the K||Cu, K||K and potassium ion batteries obtained in the above examples 1-6 are as follows:
[0061] Figure 4 The charge and discharge curves of K||Cu and K||K batteries in three ester-ether hybrid electrolytes and commercial 0.8M KPF6 / EC+DEC (0.8M KPED) electrolyte show that K||Cu has the smallest polarization voltage in 1.0M KFED, and the average coulombic efficiency (CE) after stabilization is about 97.5%, which is higher than 0.8M KPED. In contrast, the polarization of K||Cu in 1M KFVD and 1M KFPD is about 2V due to the instability of the interface and electrolyte, with greater fluctuations and lower average values, even close to 0% after 15 cycles. In the K||K symmetric battery, the cycle life of 0.8M KFED, 1M KFPD and 1M KFVD electrolytes is only 52h, 40h and 58h, respectively. The 1M KFED electrolyte provides a life of more than 200 hours. The good stability of 1M KFED electrolyte should be attributed to the formation of a stable SEI layer on K metal by this electrolyte and the significant suppression of the generation of “dead K” during K stripping / plating.
[0062] Figure 5 a and b are Raman spectra of KFSI / EC+DME electrolytes with different concentrations. Figure 5 As shown in a, at 660-780cm -1 The Raman spectrum in the range showed five distinct peaks centered at 714.0, 716.0, 0.5, 720.0, 730.0, and 740.0 cm -1 , corresponding to the free EC, solvated EC, and free FSI of CIP and AGG, respectively. -and K-FSI interaction structure. As the concentration increases from 1M to 5M, free FSI - The ratio of AGG decreased from 51.2% to 6.3%, while that of AGG increased significantly from 10.1% to 35.5%. The content of EC in the solvation sheath increased from 56% to 92%. Figure 5 b, at 800-880cm -1 There are four obvious peaks in the range of 814.0, 830.0, 849.0 and 859 cm -1 , corresponding to free and solvated DME. When the KFSI concentration increased from 1 M to 5 M, the proportion of solvated DME increased from 54.9% to 81.4%. The shift in the peak position and the change in the peak area ratio indicate that K + Enhanced coordination with solvent molecules.
[0063] Figure 5 The MD simulation results in c and d show that with the increase of the concentration of ester-ether hybrid electrolyte, K + The solvation structure of the ions changes: due to the insufficient number of solvent molecules, anion aggregation occurs, resulting in the FSI in the solvation shell. - In addition, this solvation structure with abundant anions can also provide a low energy barrier (-1.737 eV) for the desolvation process to achieve rapid K + Transfer kinetics. In summary, the AGG-dominated solvation structure in 5M KFED leads to K + With FSI - The stronger interaction with the ions leads to lower desolvation energy, resulting in faster reaction kinetics. These results also confirm that this new ester-ether hybrid electrolyte exhibits a broadly controlled solvation structure from solvent-separated ion pair (SSIP) to aggregation (AGG) dominance.
[0064] Figure 6 The charge and discharge curves of K||Cu and K||K batteries in KFED electrolytes with different concentrations. Figure 6 a It can be seen that 5M KFED has a higher CE in the first 5 cycles. More specifically, the first coulombic efficiency in 5M KFED is 79.85%, which is much higher than that of 1M, while the low CE may be due to the excessive growth of SEI and the formation of dead metal. 5M KFED shows excellent rate performance in K||Cu cells, such as Figure 6 b. In 5M electrolyte, the K||Cu battery has a peak current of 0.2, 0.5, 1.0, 1.5, 2.0 and 3.0 mA cm -2The polarization voltages at the density currents are 0.19, 0.25, 0.32, 0.36, 0.39, and 0.45 V, respectively. It can be seen that the polarization does not change significantly with the increase of current, which is due to the formation of a stable SEI interface and the fast potassium transfer kinetics of the electrolyte. The long-term cycling performance of 5MKFED was further measured using a K||K symmetric cell. Figure 6 As shown in c, negative voltage values indicate K plating, while positive voltage values indicate K stripping. The voltage hysteresis of the K||K cell in 1M KFED≈0.2V suddenly drops to around 0.1V at 142h, which is a short circuit phenomenon caused by dendrite growth. The K||K cell in 5M KFED exhibits an average voltage hysteresis around 0.04V and remains stable during the 200h cycle without obvious oscillation.
[0065] Figure 7 The figure shows the charge and discharge performance of BBD / CNT in different ester-ether hybrid electrolyte systems. It can be clearly seen that during 100 cycles, the charge and discharge curves corresponding to KFPD, KFVD and KPED electrolytes have poor overlap and severe capacity decay, but 1M KFED has the highest specific capacity and capacity retention rate.
[0066] Figure 8 The charge-discharge performance of BBD / CNT in KFSI / EC+DME ester-ether hybrid electrolyte systems with different concentrations. As the concentration increases, the overlap of the charge-discharge curves increases. The overlap of 3M and 5M electrolytes is very high, indicating that they have stable potassium storage. However, by comparing their specific capacities, it can be found that the 5M electrolyte has the highest specific capacity, which is 288 mAh g -1 .
[0067] Fig. 9 The long cycle performance and rate performance of BBD / CNT in KFSI / EC+DEM ester-ether hybrid electrolyte with different concentrations are consistent with the charge-discharge curve. -1 At a current density of 2.5 Å, BBD / CNT in 5 M KFED exhibited the highest capacity (288 mAh g -1 ) and capacity retention. When the current density is expanded to 200mA g -1 The capacity of BBD / CNT in 1M and 3M electrolytes is severely attenuated, and is relatively low in 7M electrolyte. In contrast, the electrode in 5M KFED electrolyte not only has good cycle stability, but also has a high capacity (244 mAh g) after 100 cycles. -1 )( Fig. 9b). In addition, BBD / CNT exhibits the best rate capability in 5 M KFED electrolyte with a current density of 600 mA g -1 Under the condition of 105mAh g -1 The highest specific capacity is twice that of other electrolytes.
[0068] Fig.10 a is the dissolution UV and visible light diagram of BBD / CNT in KFSI / EC+DEM ester ether hybrid electrolyte system with different concentrations, as shown in Fig.10 The insert in a shows the optical images of BBD dissolved in different concentrations of KFSI / EC+DME. It can be clearly observed that with the increase in concentration, more and more BBD precipitates appear at the bottom of the centrifuge tube. The UV-visible spectrum also verifies that the solubility of BBD has an obvious trend of change. -1 The peak intensity at decreases with increasing electrolyte concentration. This result indicates that the AGG-dominated solvation structure can significantly reduce the solubility of organic active substances in the electrolyte in high-concentration electrolytes. Low solubility ensures that BBD / CNT has good electrochemical performance.
[0069] Fig.10 b is a combustion experiment of KFSI / EC+DEM ester-ether hybrid electrolyte system with different concentrations. As the salt concentration increases, the maximum flame during the combustion process gradually becomes smaller. This is because almost all solvents are coordinated with KFSI to form an AGC-dominated solvation structure, resulting in very free solvent molecules, which makes the high-concentration electrolyte have better flame retardant properties. Good flame retardant properties ensure the safety of the battery during operation.
[0070] Fig.11 a is the pseudocapacitive contribution of BBD / CNT in different electrolytes. The pseudocapacitive contribution of BBD / CNT composites in KFSI / EC+DME ester ether hybrid electrolytes with different concentrations was calculated by variable speed CV. The surface capacitance behavior of BBD / CNT in 1M KFED at 0.2mV / s contributed less, 29.79%, which was significantly lower than other higher concentration electrolytes (49.373M, 5M and 7M KFED were 46.09%, respectively). This indicates that the pseudocapacitive K storage mechanism is enhanced with increasing electrolyte concentration. The surface capacitance contribution of these electrolytes continues to increase with increasing scan rate, which is due to the improved K adsorption behavior of CNTs, and also clearly shows that there is a significant change in the change of K storage mechanism from redox-dominated reaction to the joint control of the two K storage behaviors. The enhanced pseudocapacitive mechanism significantly improves the K storage reaction kinetics of BBD / CNT anode.
[0071] Fig.11b is the potential rise / fall η caused by the internal resistance and voltage polarization in each resting stage of the GITT test. Fig.11 In b, the calculated η in 5 M KFED is significantly lower compared with other concentrations of KFED, indicating that this reaction system has lower resistance. Fig.11 c is K calculated according to the commonly used method + Diffusion coefficient, it can be seen that the D of all electrolytes in the potassium process K + All showed similar trends, ranging from 10 -7 -10 -8 cm 2 / s. But D K + Clearly different trends emerge in low-concentration and high-concentration electrolytes, among which 5 M KFED has the largest diffusion coefficient, which is attributed to the faster interfacial conduction provided by the AGG-dominated solvation structure, enabling rapid K storage.
[0072] Fig.11 de is the electrochemical impedance spectrum (EIS) and fitting value of potassium ion half-cell in different concentrations of KFED, according to Fig.11 The equivalent circuit inserted in d is fitted. Fig.11 Fitting R in e ct It can be clearly observed that the resistance decreases significantly with the increase of electrolyte concentration from 1M to 5M, R ct It dropped from 3.7kΩ to 1.6kΩ and then increased to 3.0kΩ in 7M KFED. It is clear that after 50 cycles, the R ct The resistance of 5M KFED before and after cycling is the lowest. The reason why 5M KFED shows the lowest resistance is that the AGG-dominated dissolution structure produces a KF-rich SEI on the surface of the electrode material, allowing K + Rapid transport across the electrode surface.
Claims
1. Application of an aldehyde-based organic composite material and an optimized ester-ether hybrid electrolyte in a potassium ion battery, characterized in that: The potassium ion battery includes potassium metal, an organic negative electrode, and an electrolyte; the organic negative electrode is prepared by heat treatment using 2-bromobenzene-1,3-dicarboxaldehyde and multi-walled carbon nanotubes (CNT) as raw materials; the electrolyte is a bis(fluorosulfonyl)imide potassium salt ester ether hybrid electrolyte.
2. The use of an aldehyde-based organic composite material and an optimized ester-ether hybrid electrolyte in a potassium ion battery according to claim 1, characterized in that: Preparation of aldehyde-based organic composite materials: 2-bromobenzene-1,3-dicarboxaldehyde and multi-walled carbon nanotubes CNT were mixed and ground in a mass ratio of 1:1, and the mixture was transferred to a Schlenk tube for argon atmosphere replacement. During the heat treatment, the temperature was set to the melting point range of the organic matter, 139-144°C.
3. The use of an aldehyde-based organic composite material and an optimized ester-ether hybrid electrolyte in a potassium ion battery according to claim 1, characterized in that: Use ester-ether mixed system: select common ethylene carbonate, propylene carbonate or vinylene carbonate as the base solvent; use ethylene glycol dimethyl ether as the ether base solvent. Mix ester and ether in equal volumes as ester-ether mixed solvent, recorded as ethylene carbonate + ethylene glycol dimethyl ether, propylene carbonate + ethylene glycol dimethyl ether, vinylene carbonate + ethylene glycol dimethyl ether.
4. The use of an aldehyde-based organic composite material and an optimized ester-ether hybrid electrolyte in a potassium ion battery according to claim 1, characterized in that: Preparation of electrolyte: In a glove box filled with argon, potassium bis(fluorosulfonyl)imide was added to ethylene carbonate + ethylene glycol dimethyl ether, propylene carbonate + ethylene glycol dimethyl ether, and vinylene carbonate + ethylene glycol dimethyl ether, respectively, and stirred evenly to obtain a potassium ion battery electrolyte with a concentration of 1.0 mol / L.
5. The use of an aldehyde-based organic composite material and an optimized ester-ether hybrid electrolyte in a potassium ion battery according to claim 1, characterized in that: Adjust the electrolyte concentration: weigh salts of different masses to control the molar concentration. The prepared electrolyte concentrations were 1.0 mol / L, 3.0 mol / L, 5.0 mol / L, and 7.0 mol / L, respectively. The optimal electrolyte concentration was 5.0 mol / L.
